(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This paper analyzed how a device that functions as a safety tool for cyclists in District V, Quezon City, contributes to the overall decrease in road casualties riders face. With the continuous rise in cyclists due to the pandemic, the researchers came up with this idea and set off as pioneers in creating this kind of innovation. Since there is little to no technological device that helps in road safety available in the market to date, especially in District V, the researchers decided to innovate and provide a solution through a device. From an engineering perspective, the researchers innovated a solution to mitigate the harms bicyclists face through a device that will allow them to communicate better and safer on the road, whether they are a beginners or not. A gesture light-controlled glove with the function of giving basic road signals (left, right, stop) and GPS to track the bike’s location was created and tested to see if it could resolve some issues faced by cyclists. The results showed that the device acquired the necessary standards overall to perform its primary concepts to solve the current issue. The researchers were able to comply with the targeted goals for the device. Through structured observation and interviews, the researchers gathered data showing that the device performed its assigned functions: left, right, stop signals, and the GPS. The researchers found that many people used bicycles in Quezon City, especially those who used bicycles as a form of transportation when going to work. Data collection was conducted in May 2022 and covered District V of Quezon City. Still, due to the ongoing pandemic, several health measures were considered to avoid being at risk of COVID-19 for both the researchers’ and responders’ safety.